A Systematic Review of Pregnancy and Coronavirus Infection: Maternal, Fetal and Neonatal Outcomes - Furlan, Mara Cristina Ribeiro; Jurado, Sonia Regina; Uliana, Catchia Hermes; Silva , Maria Eduarda Pascoaloto; Nagata, Letícia Akie; Maia, Anna Clara Freitas (Revista Cuidarte, 2020)
Introduction: The effects of severe acute respiratory syndrome (SARS-CoV) during pregnancy are little known. This study aims to describe clinical outcomes in pregnant women with SARS-CoV1 and SARS-CoV2 and their impact on the health of the fetus and newborn. Materials and Methods: A systematic review was conducted using the CAPES Portal of E-Journals, Google Scholar, LILACS, and PubMed search engines. Results: 27 research articles were selected. The mortality rate was higher in pregnant women with SARS-CoV1 than those with SARS-CoV2. The most common symptoms reported by pregnant women with COVID-19 were fever and cough. Most SARS-CoV1 and SARS-Cov2 tests had negative results in infants born to mothers with confirmed COVID-19. Both types of infections caused intrauterine growth restriction and breathing problems in newborns. Discussion: SARS-CoV-1 and SARS-CoV-2 infections share common clinical features such as fever, dry cough, dyspnea, pneumonia, and admission to intensive care unit (ICU) for mechanical ventilation. Although vertical transmission of coronavirus disease 19 is not reported in the literature, IgM levels were found in blood tests from infants of mothers who had SARS-CoV-2 during pregnancy. Conclusions: Further research is needed to better understand maternal, fetal, and neonatal clinical outcomes of SARS-CoV-2 during pregnancy to contribute to the precautionary principle and therapeutic decisions on this infectionHow to cite this article: Furlan, Mara Cristina Ribeiro; Jurado, Sonia Regina; Uliana, Catchia Hermes; Silva, Maria Eduarda Pascoaloto; Nagata, Letícia Akie; Maia, Anna Clara Freitas. Gravidez e infecção por coronavírus: desfechos maternos, fetais e neonatais – Revisão sistemática. Revista Cuidarte. 2020; 11(2): e1211. http://dx.doi.org/10.15649/cuidarte.1211
Keywords: Coronavirus; Pregnancy Complications, Infectious; Infant, Newborn